Politicizing the use of glyphosate in europe: comparing policy issue linkage across advocacy organizations and countries - Tosun, Jale; Varone, Frédéric (Journal of comparative policy analysis, 2020)
The European Citizens’ Initiative enables advocacy organizations to place policy issues on the political agenda. Which frames did advocacy organizations use to mobilize the support of citizens for the initiative on banning glyphosate and to politicize this issue? The article shows for France, Germany, Italy, Portugal, and Spain that some advocacy organizations linked the issue of glyphosate to the related issue of genetically modified organisms (GMOs) and/or referred to the controversial Monsanto company in their mobilization campaigns and politicization strategies. Whether or not advocacy organizations linked glyphosate to GMOs/Monsanto was determined by their organizational goals.
Gesehen am 25.02.2021